The Financial Channel of Wage Rigidity - Schoefer, Benjamin (National Bureau of Economic Research, 2021)
I propose a financial channel of wage rigidity. In recessions, rather than propping up marginal (new hires') costs of labor, rigid average wages squeeze cash flows, forcing firms to cut hiring due to financial constraints. Indeed, empirical cash flows and profits would turn acyclical if wages were only moderately more procyclical. I study this channel in a search and matching model with financial constraints and rigid wages among incumbent workers, while new hires' wages are flexible. Individually, each feature generates no amplification. By contrast, their interaction can account for much of the empirical labor market fluctuations–breaking the neutrality of incumbents' wages for hiring, and showing that financial amplification of business cycles requires wage rigidity
10.3386/w29201
Keywords: Arbeitspapier; Graue Literatur; Lohnrigidität; Lohnbildung; Lohnniveau; Matching; Personalbeschaffung